2012
DOI: 10.1073/pnas.1200296109
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of impact markers in desert wetlands and implications for the Younger Dryas impact hypothesis

Abstract: The Younger Dryas impact hypothesis contends that an extraterrestrial object exploded over North America at 12.9 ka, initiating the Younger Dryas cold event, the extinction of many North American megafauna, and the demise of the Clovis archeological culture. Although the exact nature and location of the proposed impact or explosion remain unclear, alleged evidence for the fallout comes from multiple sites across North America and a site in Belgium. At 6 of the 10 original sites (excluding the Carolina Bays), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…The actual spherule values are almost certainly lower. In summary, we found that SEM analyses to determine microstructure and the application of a correction factor are essential, because true YDB spherules cannot be reliably identified by light microscopy alone as was attempted by Surovell et al, Pinter et al, and Pigati et al (17). and carefully collected the sediment directly beneath each chert fragment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual spherule values are almost certainly lower. In summary, we found that SEM analyses to determine microstructure and the application of a correction factor are essential, because true YDB spherules cannot be reliably identified by light microscopy alone as was attempted by Surovell et al, Pinter et al, and Pigati et al (17). and carefully collected the sediment directly beneath each chert fragment.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, determining the nature and origin of observed spherules is essential. Attempts to replicate the spherule abundances and peaks observed by (17) confirmed the presence of YDB spherules, while studies by Surovell et al (18) and Pinter et al (19) did not. Surovell et al examined sediment sequences across the YDB at seven archeological sites in North America, using radiocarbon dates and/or diagnostic cultural artifacts to identify the stratum likely to be the YDB.…”
mentioning
confidence: 87%
“…Subsequent studies (13,15,16) questioned the origins of many impact markers cited by ref. 11, but the discovery of the SLOs alongside abundant, compositionally similar microspherules in three YDB sites in North America and Asia is difficult to explain by anything other than a cosmic impact.…”
mentioning
confidence: 99%
“…The Pt peak ( Fig. 1) is unlikely to be a mass-spectrometry artifact because (a) it is smoothly defined by seven ice samples; (b) the HfO interferences ( 178 Hf 16 194,195,196 Pt isotopes, respectively, were carefully assessed; (c) the 178,179,180 Hf signals in sample 63 with the highest Pt concentration are at least a factor of 10 lower than those of 194,195,196 Pt; and (d) there is no linear correlation between Hf concentrations and Pt concentrations in the ice samples.…”
mentioning
confidence: 99%
“…The reproducibility, reliability, and validity of the impact indicators have been challenged, not least because many of these may be terrestrial in origin (possibly volcanic, organic, or detrital) and have been found in deposits younger and older than the YD (14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Others have questioned the physics of the supposed impact and whether it could or did have consequences for Late Pleistocene environments, animals, and people (26,(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%